Epigenetic regulation on left atrial function and disease recurrence after catheter ablation in atrial fibrillation - Mi-Ryung Han; Joo Hee Jeong; Yun Gi Kim; Hyun-Ho Yang; Chang-Ok Seo; Yeji Kim; Hyoung Seok Lee; Jaemin Shim; Young-Hoon Kim; Jong-Il Choi (Clinical Epigenetics)
Abstract Background Genetic variation and modifiable risk factors play a significant role in the pathogenesis of atrial fibrillation (AF). The influence of epigenetic modification on AF remains to be elucidated. We investigated the role of DNA methylation in the etiology of AF. Epigenetic evaluation was performed in 115 AF patients who underwent radiofrequency catheter ablation in a single institution. We measured methylation at approximately 850,000 bp cytosine-phosphate-guanine (CpG) sites in the 115 samples. The degree of methylation was compared across seven classification criteria: type of AF, late recurrence, impaired left atrium (LA) function, late gadolinium enhancement, LA diameter, LA volume, and flow velocity of the LA appendage. Results The four most significantly methylated genes were DEFB104B, C3, TANC1, and TMEM9B. The DEFB104B gene (cg20223677 in the transcription start site), which encodes β-defensin 104B, was hypomethylated in three groups: AF patients with late recurrence, impaired LA function, and impaired LAA flow velocity. Enriched functional annotation of the differentially methylated datasets revealed that five out of the seven AF groups in this cohort were associated with genes involved in the cell movement of endothelial cell lines, sprouting angiogenesis by endothelial cell lines, or migration of endothelial cell lines. Conclusions Epigenetic profiling revealed that epigenetic modification might affect important characteristics of AF. Our results suggest that the pathogenesis of AF might be affected by not only genetic variation or modifiable factors but also by epigenetic modulation.